2020
DOI: 10.1111/cmi.13197
|View full text |Cite|
|
Sign up to set email alerts
|

Fungal biotin homeostasis is essential for immune evasion after macrophage phagocytosis and virulence

Abstract: Biotin is an important cofactor for multiple enzymes in central metabolic processes.While many bacteria and most fungi are able to synthesise biotin de novo, Candida spp. are auxotrophic for this vitamin and thus require efficient uptake systems to facilitate biotin acquisition during infection. Here we show that Candida glabrata and Candida albicans use a largely conserved system for biotin uptake and regulation, consisting of the high-affinity biotin transporter Vht1 and the transcription factor Vhr1. Both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 82 publications
2
27
0
Order By: Relevance
“…In the four species with duplicates, the ancestral CAGL0K04565g orthologs evolved more than twice as fast as the duplicated CAGL0K04609g orthologs (Supplemental Figure 2), suggesting that the duplicates are more likely to retain the essential function in biotin transport. Recently, individual knockouts of the CAGL0K04565g and CAGL0K04609g genes in C. glabrata showed that only the latter was essential for growth in these conditions (Sprenger et al 2020), thus validating our assessments with transposon mutagenesis.…”
Section: Identification Of Essential Genessupporting
confidence: 65%
“…In the four species with duplicates, the ancestral CAGL0K04565g orthologs evolved more than twice as fast as the duplicated CAGL0K04609g orthologs (Supplemental Figure 2), suggesting that the duplicates are more likely to retain the essential function in biotin transport. Recently, individual knockouts of the CAGL0K04565g and CAGL0K04609g genes in C. glabrata showed that only the latter was essential for growth in these conditions (Sprenger et al 2020), thus validating our assessments with transposon mutagenesis.…”
Section: Identification Of Essential Genessupporting
confidence: 65%
“…In the four species with duplicates, the ancestral CAGL0K04565g orthologs evolved more than twice as fast as the duplicated CAGL0K04609g orthologs (Supplemental Figure 2), suggesting that the duplicates are more likely to retain the essential function in biotin transport. Recently, individual knockouts of the CAGL0K04565g and CAGL0K04609g genes in C. glabrata showed that only the latter was essential for growth in these conditions (32), thus validating our assessments with transposon mutagenesis.…”
Section: Identification Of Essential Genessupporting
confidence: 65%
“…In “Fungal biotin homeostasis is essential for immune evasion after macrophage phagocytosis and virulence”, which was published in Volume 22, Issue 7 July 2020 e13197 (Sprenger et al ., 2020), the authors would like to note that Figure 6a was incorrectly labelled.…”
mentioning
confidence: 99%